2002
DOI: 10.1074/jbc.c100442200
|View full text |Cite
|
Sign up to set email alerts
|

Jab1 Interacts Directly with HIF-1α and Regulates Its Stability

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a master transcription factor that controls transcriptional activation of a number of genes responsive to the low cellular oxygen tension, including vascular endothelial growth factor (VEGF), erythropoietin, and glycolytic enzymes. The stability and activity of HIF-1␣ are regulated by binding to various proteins such as pVHL, p53, and p300/CBP. Here, using the yeast two-hybrid screening system, we found that HIF-1␣ interacts with Jab1 (Jun activation domain-binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(104 citation statements)
references
References 23 publications
4
99
0
1
Order By: Relevance
“…In support of a functional relationship between VHL and JAB1, the latter could be co-immunoprecipitated with VHL in WT8 cells. Importantly, recent data suggest a further connection between JAB1 and VHL through HIF-1a (Bae et al, 2002). These investigators reported direct binding between JAB1 and HIF1a, a ecting the stability of the latter under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 96%
“…In support of a functional relationship between VHL and JAB1, the latter could be co-immunoprecipitated with VHL in WT8 cells. Importantly, recent data suggest a further connection between JAB1 and VHL through HIF-1a (Bae et al, 2002). These investigators reported direct binding between JAB1 and HIF1a, a ecting the stability of the latter under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Jab1 also binds hypoxia inducible factor-1, prevents its degradation and enhances its transcriptional activity. 28 Upregulation Figure 2 Increase of Jab1 expression in HER-2/neu-overexpressing human breast cancer cells. (a) MCF-7 (MCF) and MDA-MB-453 (453) human breast cancer cells cultured in 10% fetal calf serum medium.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the HIF-1 protein is stabilized and translocated into the nucleus [19], where it binds to HREs to regulate expression of its target genes ( Figure 2). In addition to VHL, murine double minute 2 [30] and Jab1 [31] have also been reported to affect the ubiquitination and stability of HIF-1. It should be pointed out that the protein stability and transcriptional activity of HIF-1 can be regulated by several other factors besides hypoxia, such as the accumulation of intermediate metabolites, the loss of tumor-suppressor function and the gain of oncogene function [32].…”
Section: Ubiquitin-dependent and Independent Degradation Of Hif-1 Prmentioning
confidence: 99%